Strategi Lokalisasi PKL : Peranan Pemerintah Kabupaten Pamekasan Dalam Meningkatkan Perekonomian Daerah - Maulana, Wahyu; Efendi, Junaidi; Lestari Pramita Putri, Devi (Coopetition : Jurnal Ilmiah Manajemen, 2024)
The aim of this research is to see how the localization strategy for street vendors in Pamekasan district can improve the regional economy. This is not without reason because street vendors are a form of business in the informal sector whose existence has a significant impact on the regional economy and there are efforts from the regional government itself to encourage the informal sector by achieving quite large numbers during its term of office so that this to be sustainable and synergistic. This is certainly not easy considering that there are still many problems that need to be resolved so as to provide mutually beneficial joint solutions. This research is felt urgent to be implemented considering that there is still a lot of "homework" that must be completed. The research object is the street vendor association in Pamekasan district. Qualitative descriptive method used in this research. The sampling technique for street vendors in each community uses techniques purposive sampling. The results of research regarding the localization strategy carried out by the Pamekasan district government were that a special area for street vendors (zoning model) was formed which was spread across several points including: 1. The "Sae Salera" area; 2. The "Sae Rassah" area and 3. The "Food Colony" area. It is hoped that these three areas will become one of the solutions and part of the strategy carried out by the Pamekasan district regional government.